Between Selfish And Altruistic Desires In Jodi Picoult's Novel My Sister's Keeper (2004): A Psychoanalytic Criticism - Susianti, Ana, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
This research paper is aimed to show visible image of Jodi Picoul's novel which is analyzed by using psychoanalytic criticism. The objectives of the research are to analyze the novel based on the structural elements and to analyze the novel based on psychoanalytic criticism proposed by Sigmund Freud. This research paper belongs to qualitative research. Data of the research are divided into two, primary data and secondary data. The primary data of the research is My Sister's Keeper novel and secondary data of the research are biography of the author, websites, and other source about psychoanalytic criticism that support the analysis. The method to analyze this data is descriptive analysis. The researcher comes to the conclusion as follows. Based on the psychoanalytic criticism analysis, Jodi Picoult illustrated psychological phenomena in which an individual has experienced internal and external conflict between selfish and altruistic desires. The outcome of the study shows that Jodi Picoult illustrates the psychological phenomenon when an individual experiences with her inner conflict between her different desires. She covers her conflict using selfish and altruistic desires to solve the problem.